Elevated Temperature and Allelopathy Impact Coral Recruitment. - Raphael Ritson-Williams; Cliff Ross; Valerie J Paul (PLoS ONE, 2016)
As climate change continues to alter seawater temperature and chemistry on a global scale, coral reefs show multiple signs of degradation. One natural process that could facilitate the recovery of reef ecosystems is coral recruitment, which can be influenced by the benthic organisms in a local habitat. We experimentally tested both a global stressor (increased seawater temperature) and a local stressor (exposure to microcolin A, a natural product from a common marine benthic cyanobacterium) to determine how these stressors impacted coral larval sublethal stress, survival and settlement. Larvae of Porites astreoides had the same survival and settlement as the controls after exposure to increased temperature alone, but elevated temperature did cause oxidative stress. When exposed to natural concentrations of microcolin A, larval survival and settlement were significantly reduced. When larvae were exposed to these two stressors sequentially there was no interactive effect; but when exposed to both stressors simultaneously, there was a synergistic reduction in larval survival and an increase in oxidative stress more than in either stressor treatment alone. Increased seawater temperatures made larvae more susceptible to a concurrent local stressor disrupting a key process of coral reef recovery and resilience. These results highlight the importance of understanding how interactive stressors of varying spatial scales can impact coral demographics.